Research of the Multi Parameter Edge of Chaos of Non- linear Simple Pendulum System - He Shanghong; Xie Jin; Cheng Jiefeng; Cui Qingyu (Jixie chuandong)
By using Melnikov method,the necessary condition of the chaotic motion is established through the calculation of Melnikov function. Furthermore,the edge of chaos of the dynamics system is obtained. The results are verified by the other methods of analysis chaos,such as bifurcation diagram,phase diagram,time domain waveform,and maximum Lyapunov exponent. It is demonstrated that,by using the obtained results can provide a convenient means to design a nonlinear simple pendulum with periodic motion.